Analysis of two-phase air-water annular flow in U-bends - López, J. (Heliyon, 2020)
This paper presents an experimental and numerical study of gas-liquid annular flow in horizontal 180 U-bends. The paper aims to study the effect of bend curvature radius and superficial gas velocity in the liquid film's behavior and annular flow characteristics. The study is divided into three sections. The first section corresponds to the experimental methodology and results. The second section compresses the validation of the computational fluid dynamic (CFD) model with the experimental results. Finally, the last section presents the CFD estimation of additional variables that cannot be acquired with the existing experimental setup. The experimental results provide an initial understanding of the multiphase mixture obtained using optical techniques (i.e., High-Speed Filming (HSF) analysis). The comparison between the experiments and the numerical simulations is presented, and a reasonable agreement is observed between both approaches. Finally, additional results such as film distribution and rotation before and after the bend are extracted from the CFD simulations.